The African Continental Free Trade Area and the future of investor-state dispute settlement in Africa / Mouhamed Kebe. - Kebe, Mouhamed, 1968- (Intersentia, 2023)
The African Continental Free Trade Area (AfCFTA) Agreement is at the forefront of current African business, trade and legal discussions. The future of African development, on a continental level, is largely tied to the success or failure of this agreement. One of the primary concerns of legal professionals and the international business community is the dispute settlement mechanism that will be built into the agreement. African nations are also acutely aware of the importance of developing a dispute settlement system that strikes the right balance between the interests of international investors and the needs of local populations. However, to date, there has been very little published on this topic as it pertains to the AfCFTA. While several articles look at individual components of the complex topic of African dispute settlement, there are few publications that bring together the various aspects. Individuals shaping this discussion, particularly the legal practitioners working to influence the conversation on how disputes should be carried out under the agreement, will benefit from the comprehensive look provided within the book. Not only does the author provide sound foundational knowledge as to the current landscape of dispute settlement on the continent, but he also presents a clear path forward for the negotiation of the dispute settlement provision of the AfCFTA.